John Evans papers - Evans, John, 1812-1861.
Journal (circa 200 pages; 1853 July 22-October 1) of a trip from Fort St. Pierre, S.D., to the Salmon River mountains of Idaho via Fort Benton and Fort Owen, including geological and topographical observations and sketches, comments on vegetation, game, weather, encounters with Indians, suitability of the route for railroad construction, and draft of a letter to Isaac I. Stevens, governor of Washington Territory; and letter (1857? April 26) written by Evans to his wife, Sarah Jane (Mills) Evans.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Geologist, explorer and physician.
Collection material in English.
Keywords: Evans, Sarah Jane Mills -- Correspondence; Stevens, Isaac Ingalls, -- 1818-1862 -- Correspondence; Geology -- South Dakota; Geology -- Idaho; Indians of North America -- Idaho; Indians of North America -- Montana; Indians of North America -- South Dakota; Railroads -- Surveying; Fort Benton (Mont.); Fort Owen (Mont.); Fort Pierre (S.D.); Idaho -- Discovery and exploration; Idaho -- Surveys; Montana -- Discovery and exploration; Salmon River, Middle Fork (Idaho); South Dakota -- Discovery and exploration; South Dakota -- Surveys; Explorers; Geologists; Physicians